Conditions and how to build a good test under teaching according to pedagogy approach competencies - djellab, mosbah; khatout, ramdane (Journal of Social Sciences and Humanities, 2019)
The aim of this study is to highlight and address the most important aspects related to the most important tool of educational evaluation, namely, the test, where we will try to highlight the importance of testing for the process of educational evaluation, especially under the teaching in accordance with pedagogy approach competencies, and we will try to focus on the conditions that determine how to build the test as well as the most important The general principles for the preparation of tests, and then we will address the most important types of tests. The study dealt with the most important aspects of the problems of educational evaluation, including pedagogy, psychology, etc., in addition to the most important difficulties in preparing the test and preparing his questions in light of the approach competencies. The results of the study indicate that there is a great need to train the professor on how to prepare a good test, as well as knowledge of the conditions of its construction, and this is because the test plays a pivotal role in the evaluation process as well as educational process learning in general, in addition to the effects left in the psyche of the student, Whether positive or negative. In the light of these findings, the study concluded with a set of recommendations, most notably the importance of the professor's ability to prepare and build the test, as well as continuous training and knowledge of the modern strategies of the educational evaluation process. Especially the specialists in the field of educational evaluation, and recommended the study of the need to exploit information and communication technologies, especially in the field of educational evaluation.